A Sub-Nanostructural Transformable Nanozyme for Tumor Photocatalytic Therapy - Hu, Xi; Wang, Nan; Guo, Xia; Liang, Zeyu; Sun, Heng; Liao, Hongwei; Xia, Fan; Guan, Yunan; Lee, Jiyoung; Ling, Daishun; Li, Fangyuan (Nano-Micro Letters, 2022)
The structural change-mediated catalytic activity regulation plays a significant role in the biological functions of natural enzymes. However, there is virtually no artificial nanozyme reported that can achieve natural enzyme-like stringent spatiotemporal structure-based catalytic activity regulation. Here, we report a sub-nanostructural transformable gold@ceria (STGC-PEG) nanozyme that performs tunable catalytic activities via near-infrared (NIR) light-mediated sub-nanostructural transformation. The gold core in STGC-PEG can generate energetic hot electrons upon NIR irradiation, wherein an internal sub-nanostructural transformation is initiated by the conversion between CeO2 and electron-rich state of CeO2−x, and active oxygen vacancies generation via the hot-electron injection. Interestingly, the sub-nanostructural transformation of STGC-PEG enhances peroxidase-like activity and unprecedentedly activates plasmon-promoted oxidase-like activity, allowing highly efficient low-power NIR light (50 mW cm−2)-activated photocatalytic therapy of tumors. Our atomic-level design and fabrication provide a platform to precisely regulate the catalytic activities of nanozymes via a light-mediated sub-nanostructural transformation, approaching natural enzyme-like activity control in complex living systems. Highlights: 1 An internal sub-nanostructural transformation of sub-nanostructural transformable gold@ceria (STGC-PEG) is initiated by the conversion between CeO2 and electron-rich state of CeO2−x, and active oxygen vacancies generation via the hot-electron injection from gold to ceria. 2 The sub-nanostructural transformation of STGC-PEG enhances the peroxidase-like activity and activates the plasmon-promoted oxidase-like activity, resulting in an augmented reactive oxygen species output. 3 STGC-PEG successfully achieves excellent low power (50 mW cm−2) near-infrared light-activated photocatalytic ablation of tumors in vivo.